Environmental cues and genes involved in establishment of the superinfective Pf4 phage of Pseudomonas aeruginosa - Hui, Janice G. K.; Mai-Prochnow, Anne; Kjelleberg, Staffan; McDougald, Diane; Rice, Scott A. (Frontiers in Microbiology, 2014)
Biofilm development in Pseudomonas aeruginosa is in part dependent on a filamentous phage, Pf4, which contributes to biofilm maturation, cell death, dispersal and variant formation, e.g. small colony variants. These biofilm phenotypes correlate with the conversion of the Pf4 phage into a superinfective variant that reinfects and kills the prophage carrying host, in contrast to other filamentous phage that normally replicate without killing their host. Here we have investigated the physiological cues and genes that may be responsible for this conversion. Flow through biofilms typically developed superinfective phage around day 4 or 5 of development and corresponded with dispersal. Starvation for carbon or nitrogen did not lead to the development of superinfective phage. In contrast, exposure of the biofilm to nitric oxide, H2O2 or the DNA damaging agent, mitomycin C, reproducibly led to an increase in the superinfective phage, suggesting that reactive oxygen or nitrogen species (RONS) played a role in the formation of superinfective phage. In support of this, an oxyR mutant, the major oxidative stress regulator in P. aeruginosa, displayed significantly higher and earlier superinfection than the wild-type. Similarly, inactivation of mutS, a DNA mismatch repair gene, resulted in an early and a four log increase in the amount of superinfective phage generated by the biofilm. In contrast, loss of recA, important for DNA repair and SOS response, also resulted in a delayed and decreased production of superinfective phage. Treatments or mutations that increased superinfection also correlated with an increase in the production of morphotypic variants. The results suggest that the accumulation of RONS by the biofilm may result in DNA lesions in the Pf4 phage, leading to the formation of superinfective phage, which subsequently selects for morphotypic variants, such as small colony variants.